Synthesis and characterization of heterogeneous magnetic bifunctional catalyst derived from rice husk for biodiesel production from used cooking oil - Hazmi, Balkis (2021)
The heterogeneous magnetic bifunctional catalysts supported on rice husk biochar were successfully synthesized by impregnated K2O and magnetic compound Fe2O3 and NiO. The synthesized catalysts were characterized by using XRD, BET, TPD-CO2, TPD-NH3, TGA-DTA, FTIR, FESEM-EDX and VSM. The prepared catalysts consisted with high surface area more than 20 m²g⁻¹ with highly porous structure that increased the number of active sites, overcame diffusion problem between solid catalyst-oil-methanol and enhanced the catalytic transesterification. The utilization of magnetic catalyst is known to ease separation process from reaction medium by introduce magnetic field. The VSM analysis revealed that RHC/K2O-20 wt.%/Fe-5 wt.% and RHC/K2O-20 wt.%/Ni-5 wt.% exhibited sufficient magnetism of 7.88 emug-1 and 2.31 emug-1 respectively for separation of catalyst. Furthermore, the recovery percentage of magnetic catalysts were recorded approximately more than 80 % after reaction was catalyzed 6 times. In this study, the catalysts were used for transesterification of used cooking oil (UCO) to biodiesel by using a conventional reflux. The catalytic activities of RHC/K2O-20 wt.%/Fe-5 wt.% and RHC/K2O-20 wt.%/Ni-5 wt.% had demonstrated the highest biodiesel yield at 98.6% and 98.2% under following moderate optimum condition: catalyst loading 4wt.%, methanol-to-molar ratio of 12:1, reaction temperature of 75 oC and 65 oC within reaction time of 4 h and 2 h respectively. Both catalysts were reused for 5 transesterification consecutive cycles with a biodiesel yield more than 70.0 %. The fuel properties of the biodiesel reviewed by the ASTMD 6751 method, and it was found to be within allowable limits and has properties almost similar to diesel fuel. To conclude, both of heterogeneous magnetic bifunctional catalysts RHC/K2O-20 wt.%/Fe-5 wt.% and RHC/K2O-20 wt.%/Ni-5 wt.% have the potential in the transesterification of low-grade feedstocks due to high catalytic performance, recovery, reusability, and stability.